2017
DOI: 10.1177/2396987317719362
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial mechanical thrombectomy stent retrievers and aspiration devices in the treatment of acute ischaemic stroke: A systematic review and meta-analysis with trial sequential analysis

Abstract: Purpose: Intra-arterial mechanical thrombectomy combined with appropriate patient selection (image-based selection of acute ischaemic stroke patients with large artery occlusion) yields improved clinical outcomes. We conducted a systematic review and meta-analysis, with trial sequential analysis to understand the benefits, risks and impact of new trials reporting in 2016 on the magnitude/certainty of the estimates for clinical effectiveness and safety of mechanical thrombectomy. Method: Random effects' models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…To identify a large pool of potential survey recipients who were neuro-interventionalists or noninterventional vascular neurologists with expertise in modern endovascular thrombectomy care, we examined the study center listings in 15 recent large, multicenter endovascular thrombectomy studies, including the eight randomized superiority-design trials of endovascular mechanical thrombectomy vs. medical therapy alone identified in a recent systematic review (MR CLEAN, ESCAPE, SWIFT-PRIME, EXTEND-IA, REVASCAT, THRACE, PISTE, THERAPY) ( 17 ), one superiority design trial comparing contact aspiration vs. stent retriever (ASTER) as well as the four controlled noninferiority design trials comparing different endovascular mechanical thrombectomy techniques identified in another recent systematic review (SWIFT, TREVO 2, Penumbra-3D, ARISE II) ( 14 ), and three recent large multicenter observational studies in the United States (TRACK, STRATIS, NASA). For each study, we identified the 10 highest enrolling centers and, for those centers, abstracted the names of (1) the site principal investigator, (2) the site co-investigator whose last name was earliest in alphabetic order, and (3) the site co-investigator whose last name was last in alphabetic order.…”
Section: Methodsmentioning
confidence: 99%
“…To identify a large pool of potential survey recipients who were neuro-interventionalists or noninterventional vascular neurologists with expertise in modern endovascular thrombectomy care, we examined the study center listings in 15 recent large, multicenter endovascular thrombectomy studies, including the eight randomized superiority-design trials of endovascular mechanical thrombectomy vs. medical therapy alone identified in a recent systematic review (MR CLEAN, ESCAPE, SWIFT-PRIME, EXTEND-IA, REVASCAT, THRACE, PISTE, THERAPY) ( 17 ), one superiority design trial comparing contact aspiration vs. stent retriever (ASTER) as well as the four controlled noninferiority design trials comparing different endovascular mechanical thrombectomy techniques identified in another recent systematic review (SWIFT, TREVO 2, Penumbra-3D, ARISE II) ( 14 ), and three recent large multicenter observational studies in the United States (TRACK, STRATIS, NASA). For each study, we identified the 10 highest enrolling centers and, for those centers, abstracted the names of (1) the site principal investigator, (2) the site co-investigator whose last name was earliest in alphabetic order, and (3) the site co-investigator whose last name was last in alphabetic order.…”
Section: Methodsmentioning
confidence: 99%
“…To improve recanalization rates and to overcome the well-known limitations of endovascular MT, different alternative techniques for mechanical thrombectomy have been proposed and tested 6,10 . However, to the best of our knowledge no studies have investigated differently shaped tips of the DAC.…”
mentioning
confidence: 99%
“…Of patients with acute ischaemic stroke, approximately 40% have a large vessel occlusion (LVO) [5] . More recently mechanical thrombectomy (MT) has shown substantially improved clinical outcomes for patients with LVO [6] . MT is effective up to 6 hours or more after stroke onset, depending on patient selection, but also demonstrates steeply reducing benefit with increasing time from stroke onset [7,8] .…”
Section: Introductionmentioning
confidence: 99%